Proceedings of the Proceedings of the 2nd International Conference on Social Sciences and Interdisciplinary Studies (Formerly I 2019
DOI: 10.4108/eai.24-10-2019.2290566
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Intercultural Communication Competencies into Foreign Languages Learning in the Industrial Revolution Era 4.0

Abstract: The abstract should In the era of the fourth industrial revolution today, the interaction between countries and cultures are no longer confined to overt geographical barriers due to technological advancement. However, these advances have created a countervailing effect on cultural identity, with a tendency to its loss; as well as cultural hegemony of one culture upon another culture. This phenomenon could be seen as well among foreign language learners. This critical literature study aims to examine the urgenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Meanwhile, a plethora of studies which discuss IC have been investigated by several researchers in the Indonesian context (Abduh & Rosmaladewi, 2018;Adi, 2017;Aprianoto & Haerazi, 2019;Dollah, Syarifuddin, Abduh, Amirullah, Talib, 2017;Edi, Wello, & Dollah, 2017;Haerazi, Irwansyah, Dedi & Azis, 2018;Idris, 2020;Idris & Widyantoro, 2019;Luthfia, Rosidah, & Sofian, 2019;Miftakh, 2017;Mumu, 2017;Rosyidi & Purwati, 2018;Sabilah, 2018;Siregar, 2016;Yulianti, 2019;Zacharias, 2005); however, limited studies discussing this amid COVID-19 pandemic was found. Thus, to fill the gap of the previous related studies, it is deemed necessary to carry out a study concerning this area, i.e., challenges and opportunities encountered in intercultural language teaching, particularly during the COVID-19 pandemic based on the teachers' perspectives since they are the primary executor of the instruction conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a plethora of studies which discuss IC have been investigated by several researchers in the Indonesian context (Abduh & Rosmaladewi, 2018;Adi, 2017;Aprianoto & Haerazi, 2019;Dollah, Syarifuddin, Abduh, Amirullah, Talib, 2017;Edi, Wello, & Dollah, 2017;Haerazi, Irwansyah, Dedi & Azis, 2018;Idris, 2020;Idris & Widyantoro, 2019;Luthfia, Rosidah, & Sofian, 2019;Miftakh, 2017;Mumu, 2017;Rosyidi & Purwati, 2018;Sabilah, 2018;Siregar, 2016;Yulianti, 2019;Zacharias, 2005); however, limited studies discussing this amid COVID-19 pandemic was found. Thus, to fill the gap of the previous related studies, it is deemed necessary to carry out a study concerning this area, i.e., challenges and opportunities encountered in intercultural language teaching, particularly during the COVID-19 pandemic based on the teachers' perspectives since they are the primary executor of the instruction conducted.…”
Section: Introductionmentioning
confidence: 99%